Rekonfigurasi Prosedur Penyidikan dan Perlindungan Tersangka dalam KUHAP Baru (Undang-Undang Nomor 20 Tahun 2025) - Ilham Hibatul Hakim; Ujuh Juhana (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
Law Number 20 of 2025 introduced a new Indonesian Criminal Procedure Code, replacing Law Number 8 of 1981 after more than forty years of application. The previous framework was widely criticized for limited judicial oversight, arbitrary suspect designation, and insufficient protection of suspects during criminal investigations. This study examines how the new legislation restructures investigative procedures and evaluates its impact on safeguarding suspects’ procedural rights. Employing normative legal research, the study applies statutory, conceptual, and comparative approaches. Primary legal materials include Law Number 20 of 2025, Law Number 8 of 1981, and Constitutional Court Decision Number 21/PUU-XII/2014, while secondary materials consist of scholarly books, journal articles, and legal commentaries. Data were collected through document analysis and examined using descriptive and comparative qualitative methods. The findings show that the new Code establishes clearer procedural standards by regulating nine coercive measures, requiring at least two valid pieces of evidence and a formal case exposition before suspect determination, guaranteeing legal assistance from the beginning of the investigation, and requiring audiovisual recording of examinations. Although the proposal for a preliminary examining judge was omitted, Article 158 expands pre-trial review to include unlawful seizure, unreasonable investigative delay, and detention suspension. These reforms enhance due process and accountability, yet judicial supervision remains predominantly reactive, while outdated implementing regulations continue to create practical inconsistencies and normative uncertainty.